STRATEGI PENGELOLAAN ANGGARAN UNTUK MENINGKATKAN AKUNTABILITAS DAN TRANSPARANSI BANTUAN OPERASIONAL SEKOLAH DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nur Latifa; Ngarmi Ngarmi; Sutrisno Sutrisno (STKIP Pesisir Selatan, 2026)
This study aims to identify budget management strategies to strengthen accountability and transparency in the use of School Operational Assistance (BOS) funds in elementary schools. The study is based on the urgency of monitoring public funds to ensure effective learning and compliance with statutory provisions. The study used a Systematic Literature Review (SLR) guided by PRISMA to identify, filter, assess eligibility, and synthesize relevant research evidence. Twenty-five selected sources on BOS management and education financing governance were included. The synthesis shows that accountability and transparency are improved through evidence-based participatory planning through the School Work Plan and Budget (RKAS), standardized digital financial reporting, regular information disclosure, and multi-stakeholder oversight involving principals, treasurers, teachers, school committees, parents, and local governments. Practical implications include strengthening treasurer capacity, simplifying documents, and synergizing cross-agency oversight. The study offers an integrative framework that connects governance, digital administration, and stakeholder collaboration to improve BOS accountability and transparency, with the note that the findings are a synthesis of the literature and therefore require testing and adjustment to the school context.